The progressive onset of cholinergic and adrenergic control of heart rate during development in the green iguana, Iguana iguana - Sartori, Marina R. [UNESP] (2015)
The autonomic control of heart rate was studied throughout development in embryos of the green iguana, Iguana iguana by applying receptor agonists and antagonists of the parasympathetic and sympathetic systems. Acetylcholine (Ach) slowed or stopped the heart and atropine antagonized the response to Ach indicating the presence of muscarinic cholinoceptors on the heart of early embryos. However, atropine injections had no impact on heart rate until immediately before hatching, when it increased heart rate by 15%. This cholinergic tonus increased to 34% in hatchlings and dropped to 24% in adult iguanas. Although epinephrine was without effect, injection of propranolol slowed the heart throughout development, indicating the presence of beta-adrenergic receptors on the heart of early embryos, possibly stimulated by high levels of circulating catecholamines. The calculated excitatory tonus varied between 33% and 68% until immediately before hatching when it fell to 25% and 29%, a level retained in hatchlings and adults. Hypoxia caused a bradycardia in early embryos that was unaffected by injection of atropine indicating that hypoxia has a direct effect upon the heart. In later embryos and hatchlings hypoxia caused a tachycardia that was unaffected by injection of atropine. Subsequent injection of propranolol reduced heart rate both uncovering a hypoxic bradycardia in late embryos and abolishing tachycardia in hatchlings. Hypercapnia was without effect on heart rate in late stage embryos and in hatchlings. (C) 2015 Elsevier Inc All rights reserved.